Impact of the COVID-19 pandemic on antibiotic utilization in a tertiary hospital - Burcu Çalişkan Demirkiran; Hanefi C Gül; Hakan Erdem (Journal of Infection in Developing Countries)
Introduction: This study aimed to determine the use of antimicrobial drugs during the second year of the coronavirus disease 2019 (COVID-19) pandemic, and evaluate the pandemic`s impact on antibiotic use by comparing with the pre-pandemic period.